Quality assurance of elementary schools in Sintang regency - Haura Sekarndary; Nurtanio Agus Purwanto (Universitas Papua, 2026)
Quality assurance as a process to maintain and improve the quality of education. It is necessary to understand more deeply how schools develop and implement relevant programs so that quality education is created, especially at the primary school level in the district. The research took place in 8 primary schools spread across 7 sub-districts. This is a qualitative research using in-depth interviews, observation and document analysis. The results showed that, although some schools have succeeded in developing a quality assurance program with the stages of Identify, Reflect and Fix (IRB) with an education report card, there are still significant challenges such as limited facilities and human resources as well as the lack of socio-economic status of the parents of students so that they lack the role to encourage children to learn and be ethical. The commitment of the principal, quality assurance team, and competent teachers, as well as the involvement of parents can improve school quality, as well as the contribution of the Sintang education office with strategies in the form of forming learning communities, emphasizing principals to strengthen evaluation, and encouraging teachers to improve their competence to help the success of quality assurance in Sintang District which is far from the city center.